Giddensova teorija strukturacije: zagate teoretskega eklekticizma - Stanković, Peter (Teorija in praksa, 2000)
One of the most important shifts which have occured in the sociological theory in recent decades, is intensive focus on the search for analytical solutions in order to overcome 'reductionisms' of classical sociology. Most common strategy employed by the sociologists in this context is theoretical synthesis or integration of different metatheoretical assumptions and levels of analysis. Implicit assumption behind this is that such endeavours should bring sociological theory to the state of greater complexity, and consequently, to the advanced stage of theorizing. However, on the example of the Anthony Giddens' structuration theory the author argues that successful theoretical integration or synthesis does not necesserily mean already a heuristically strong theory. Namely, Giddens has in his integrative zeal combined so many different theoretical concepts and solutions from vast variety of the sociological and philosophical traditions that his theory seriously lacks coherent and meaningful causal relations between the accumulated notions. According to this the author concludes that in attempts at theoretical synthesis and integration much greater deal of attention should be devoted to the issue of logical coherence and meaningful relations between the newly established links between the concepts.
Keywords: Giddens, Anthony; eklekticizem; družbene vede; družbena struktura; teorije